Bovine Trichomonosis Cases in the United States 2015–2019 - Martin, Katy A.; Henderson, Juli; Brewer, Matthew T. (Frontiers in Veterinary Science, 2021)
Tritrichomonas foetus is a sexually-transmitted protozoan parasite that causes early embryonic death in cattle. T. foetus is enzootic in the United States but is not a reportable disease at the national level. Thus, it is difficult to understand the prevalence and relative distribution of the disease for the purpose of developing appropriate control measures. In this study, a survey of state veterinarians was used to determine the number of reported cases in each state from 2015-2019. Our investigation revealed infections in 25 different states and a total of 3,817 reported cases nationwide. Infections occurred throughout different regions of the country, and numbers of cases were only weakly correlated with total number of cattle in each state. T. foetus is a significant pathogen in the United States and understanding the relative distribution of the parasite is useful for prioritizing surveillance and intervention strategies going forward.